The artistic interpretation of biographical facts in L. Petrusevskaya’s Ninth Volume - Kalafatics, Zsuzsanna (Slavica, 2024)
The paper deals with the interpenetrability of the boundaries between artistic prose and autobiography and documentary. By analyzing Petrushevskaya’s Ninth Volume, the paper examines how the rhetorical tropes of fiction operate in a text that is essentially autobiographical in nature, mixing different genres, and how archetypal, psychological and literary patterns are projected onto the biographical material. The cyclical arrangement of texts belonging to different periods and the blending of different discourses create the figure of a special autobiographical hero reflecting on the work.